Time Trends and Demographic Disparities in Helicobacter pylori Burden in a Large, Community-Based Population in the United States - Dan Li; Sophie A. Merchant; Jessica M. Badalov; Douglas A. Corley (Gastro Hep Advances, 2024)
Background and Aims: There are minimal recent population-based data on the epidemiology of Helicobacter pylori (H. pylori) in the United States. Methods: This retrospective cohort study evaluated H. pylori positivity rates in adult members of a large, community-based US population in 2000–2019. Time trends, demographic disparities, and birth cohort effects on H. pylori test positivity rates were analyzed. Results: Among 751,322 individuals tested for H. pylori, the overall nonserological and serological test positivity rates were 18.2% (95% confidence interval [CI], 18.1%–18.4%) and 36.8% (95% CI, 36.6%–36.9%), respectively. Nonserological positivity rate (95% CI) was significantly higher among Asian (23.2% [22.8%–23.6%]), Black (25.1% [24.4%–25.8%]), and Hispanic (28.1% [27.7%–28.5%]) individuals than non-Hispanic White individuals (10.0% [9.8%–10.2%]), and was significantly higher among individuals with a non-English language preference (32.9% [32.3%–33.5%]) than those with English language preference (15.8% [15.6%–15.9%]). Patterns were similar for serological positivity, although with substantially higher rates. Serological positivity rates decreased over 2 decades but nonserological positivity rates initially decreased and then stabilized over the past decade. There was a significant decrease in both nonserological and serological positivity rates from older to younger birth cohorts. Older age, non-White race or Hispanic ethnicity, male sex, and non-English language preference were associated with high odds of H. pylori positivity. Conclusion: The burden of H. pylori decreased over 2 decades, although the rates of active infection plateaued over the past decade in a diverse, community-based US population, likely attributable to birth cohort effects and demographic changes. Asian, Black, and Hispanic individuals had 2–3-fold higher rates of active H. pylori infection than non-Hispanic White individuals. These findings should inform targeted screening and eradication of H. pylori in high-risk US populations.